“Chimeric Pasts, Presents, and Futures”: Review of Animals in the Anthropocene: Critical Perspectives on Non-Human Futures, edited by the Human Animal Research Network Editorial Collective - Dolle, Christopher (Humanimalia, 2021)
Human Animal Research Network Editorial Collective, ed. Animals in the Anthropocene: Critical Perspectives on Non-Human Futures. Sydney: Sydney University Press, 2015. 296 pp. 35.